2016
DOI: 10.1111/pce.12801
|View full text |Cite
|
Sign up to set email alerts
|

Carbon source–sink limitations differ between two species with contrasting growth strategies

Abstract: Understanding how carbon source and sink strengths limit plant growth is a critical knowledge gap that hinders efforts to maximize crop yield. We investigated how differences in growth rate arise from source–sink limitations, using a model system comparing a fast‐growing domesticated annual barley (Hordeum vulgare cv. NFC Tipple) with a slow‐growing wild perennial relative (Hordeum bulbosum). Source strength was manipulated by growing plants at sub‐ambient and elevated CO2 concentrations ([CO2]). Limitations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 58 publications
5
51
1
Order By: Relevance
“…This result suggests that genotypes with the higher constitutive sink capacity also had greater sink plasticity. In fact, studies reported a close correlation between adaptation to CO 2 enrichment and higher sink plasticity (Atwell, Kriedemann, & Turnbull, ; Burnett et al, ; Dahal et al, ; Kikuchi et al, ). However, to our knowledge, the genotypic covariation between sink strength and plasticity was never pointed out, in particular for traits involved in different phenological phases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result suggests that genotypes with the higher constitutive sink capacity also had greater sink plasticity. In fact, studies reported a close correlation between adaptation to CO 2 enrichment and higher sink plasticity (Atwell, Kriedemann, & Turnbull, ; Burnett et al, ; Dahal et al, ; Kikuchi et al, ). However, to our knowledge, the genotypic covariation between sink strength and plasticity was never pointed out, in particular for traits involved in different phenological phases.…”
Section: Discussionmentioning
confidence: 95%
“…However, an increase in photosynthesis under e‐CO 2 was not systematically associated with an increase in grain yield (Ainsworth, ; Hasegawa et al, ; Kobayashi et al, ; Leakey et al, ; Long, Ainsworth, Leakey, Nösberger, & Ort, ; Long et al, ; Wang et al, ). One of the main hypotheses to explain this observation is that not only C source capacity but also C sink capacity drives crop production, and that either source or sink capacity alone cannot explain e‐CO 2 impacts on yield (Burnett, Rogers, Rees, & Osborne, ; Körner, ; Ludewig & Sonnewald, ; Sonnewald & Fernie, ).…”
Section: Introductionmentioning
confidence: 99%
“…These points fit well the 20-year-old observation by Hardwick [98], that rates of photosynthesis tend to follow seed development in grain legumes, rather than the reverse. Coupled with evidence that enhanced N transport to seeds promotes growth, and that the carbon:N ratio of phloem sap of legumes is generally conserved, it is reasonable to propose that engineering an enhanced ability to store N in seeds could well enhance rates of carbon fixation by legumes, a variant of the well-known, and increasingly well-elucidated, sink limitation of photosynthesis (Box 2) [99][100][101]. Box …”
Section: Water Use Efficiency Of Grain Legume Versus Non-legume Cropsmentioning
confidence: 99%
“…The effects of the sink-source relationship in photosynthesis for plants grown under elevated [CO 2 ] conditions has been previously studied, most of the time in enclosed environments such as greenhouses, growth chambers and open-top chambers and often with potted plants (e.g., von Caemmerer and Farquhar, 1984; Arp, 1991; McConnaughay et al, 1993; Farage et al, 1998; Ainsworth and Rogers, 2007; Burnett et al, 2016). The use of pots can restrict the growth of sinks organs, like roots (Arp, 1991), and thus be a poor surrogate for understanding impacts of elevated [CO 2 ] on field crops.…”
Section: Introductionmentioning
confidence: 99%